Free communication: from Soviet future cities to kitchen conversations. Issue 5 (4th July 2019) - Kurg, Andres
Abstract : This article looks at discussions of communist urban planning in relation to both the Marxist theory of ideology and communication theory in the 1960s in the Soviet Union, and the ways in which these discussions were continued in the so-called paper architecture of the 1980s. The central keyword in these discussions is the Russian term obshchenie, referring simultaneously to intercommunication, conversation, and communality. Central to investigations of informal life practices in the late Soviet context, obshchenie has been described as a means of creating a distance from the official world, a way to reach distinct interiority and a sense of authenticity that has generally been associated with the domestic and the private sphere. I will juxtapose this anthropological viewpoint of obshchenie with the way this term was used in the 1960s in the works on the future communist city by the NER group in Moscow. Finally, I will bring this trajectory together with discussions through the paper architecture of the 1980s and ask if we could view these works as sites of struggle over the meaning of obshchenie on the eve of Perestroika.